PENGARUH PELATIHAN DAN LINGKUNGAN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI BAGIAN INSTALASI HIGIENE SANITASI DI RUMAH SAKIT UMUM DAERAH dr. R. SOETRASNO REMBANG - Fitriayanto, Eko; Nurhidayati, Anik (potensio, 2013)
The research aims to test the effect of training and job environment to job effectiveness. This research uses the entire population of the employee hygiene and sanitation installations RSUD Â as many as 40 people. Results of reserach refer that the training and job environment have an influence positive significant to job effectiveness. In addition, the results also refer that the training and job environment have an influence positive significant together to job effectiveness.Â Key word: Training, job environment, job effectiveness